If it's not what You are looking for type in the equation solver your own equation and let us solve it.
23=3+(x+1)*2
We move all terms to the left:
23-(3+(x+1)*2)=0
We calculate terms in parentheses: -(3+(x+1)*2), so:We get rid of parentheses
3+(x+1)*2
determiningTheFunctionDomain (x+1)*2+3
We multiply parentheses
2x+2+3
We add all the numbers together, and all the variables
2x+5
Back to the equation:
-(2x+5)
-2x-5+23=0
We add all the numbers together, and all the variables
-2x+18=0
We move all terms containing x to the left, all other terms to the right
-2x=-18
x=-18/-2
x=+9
| -5x-3x+8=12 | | 7(6x+7)=3(9x-16) | | 3y+6+12=0 | | 3x-9=(7x+7) | | 3/x+6=8 | | 4x-9=4(7x+7) | | 4x+8=5(6x+7) | | 3x-3=3(2x-6) | | -35=6y-5 | | 10y=8+4 | | 26=5+n | | X^2+4x-1=6/x | | 20*x=18(1.5+x) | | m=3-10 | | Xx4-3=11 | | 1/10t+7=7 | | 0.3p=p | | k/6+4=7 | | 17x-3=12x+27 | | 3/x+2-4/2x-5=0 | | x^2+8=16-2x | | 3,2y+4=10 | | 4(x5)=3x+2 | | x^2-9x-4=1 | | x*(x+2)=840 | | 1-2u+u+4=0 | | -14t-35=-49 | | -7(4w+1)=-49 | | 4/t-10=6/t-10 | | 4u+5=8 | | x^2(2-x)+(x-2)^3=-5(1-2x)+(2x+1)(1-2x) | | x*2(2-x)+(x-2)*3=-5(1-2x)+(2x+1)(1-2x) |